Comparative structure analysis of the ETSi domain of ERG3 and its complex with the E74 promoter DNA sequence. Issue 10 (3rd October 2018) - Sharma, Ruby; Gangwar, Shanti P.; Saxena, Ajay K.
Abstract : X‐ray structures of the ETSi domain of human ERG3 and of its complex with the E74 promoter DNA sequence are reported. Comparison of the ETSi–DNA9 structure with known structures of ETS class 1 protein–DNA complexes shows the similarities and differences in the promoter DNA binding and specificity of the class 1 ETS proteins. Abstract : ERG3 (ETS‐related gene) is a member of the ETS (erythroblast transformation‐specific) family of transcription factors, which contain a highly conserved DNA‐binding domain. The ETS family of transcription factors differ in their binding to promoter DNA sequences, and the mechanism of their DNA‐sequence discrimination is little known. In the current study, crystals of the ETSi domain (the ETS domain of ERG3 containing a CID motif) in space group P 41 21 2 and of its complex with the E74 DNA sequence (DNA9 ) in space group C 2221 were obtained and their structures were determined. Comparative structure analysis of the ETSi domain and its complex with DNA9 with previously determined structures of the ERGi domain (the ETS domain of ERG containing inhibitory motifs) in space group P 65 21 2 and of the ERGi–DNA12 complex in space group P 41 21 2 were performed. The ETSi domain is observed as a homodimer in solution as well as in the crystallographic asymmetric unit. Superposition of the structure of the ETSi domain on that of the ERGi domain showed a major conformational change at the C‐terminal DNA‐binding autoinhibitory (CID) motif, while minor changes are observed in the loop regions of the ETSi‐domain structure. The ETSi–DNA9 complex in space group C 2221 forms a structure that is quite similar to that of the ERG–DNA12 complex in space group P 41 21 2. Upon superposition of the complexes, major conformational changes are observed at the 5′ and 3′ ends of DNA9, while the conformation of the core GGA nucleotides was quite conserved. Comparison of the ETSi–DNA9 structure with known structures of ETS class 1 protein–DNA complexes shows the similarities and differences in the promoter DNA binding and specificity of the class 1 ETS proteins.